Involvement of autophagy in ovarian cancer: a working hypothesis - Peracchio Claudia; Alabiso Oscar; Valente Guido; Isidoro Ciro (BMC, 2012)
Abstract Autophagy is a lysosomal-driven catabolic process that contributes to preserve cell and tissue homeostases through the regular elimination of damaged, aged and redundant self-constituents. In normal cells, autophagy protects from DNA mutation and carcinogenesis by preventive elimination of pro-oxidative mitochondria and protein aggregates. Mutations in oncogenes and oncosuppressor genes dysregulate autophagy. Up-regulated autophagy may confer chemo- and radio-resistance to cancer cells, and also a pro-survival advantage in cancer cells experiencing oxygen and nutrient shortage. This fact is the rationale for using autophagy inhibitors along with anti-neoplastic therapies. Yet, aberrant hyper-induction of autophagy can lead to cell death, and this phenomenon could also be exploited for cancer therapy. The actual level of autophagy in the cancer cell is greatly affected by vascularization, inflammation, and stromal cell infiltration. In addition, small non-coding microRNAs have recently emerged as important epigenetic modulators of autophagy. The present review focuses on the potential involvement of macroautophagy, and on its genetic and epigenetic regulation, in ovarian cancer pathogenesis and progression.